The influence of work related factors on job stress among officers in the Sabah headquarters of the immigration department of Malaysia (JIM Sabah) - K Vishnutharan A/L Kalimuthu (2016)
The objective of the study was to investigate the influence of work related factors on job stress among the immigration officers at the headquarters of the Immigration department of Malaysia in Sabah. The independent variables were job demand, supervisor-subordinates relationship and role ambiguity (work related factor). Personality (type A and type B) were investigated as moderator between work related factors and stress. Data for this study were collected through Occupational Stress Indicator (OSI) questionnaires. A total of 139 officers in the Sabah Immigration headquarters returned the questionnaires within the stipulated time. The result indicated that job demand has positive and significant relationship with stress with standard coefficient beta (B= 0.188), while t-value is 2.081 at p>0.05, whereas supervisor-subordinate relationship and role ambiguity shown not positive, further indicating no significant relationship to stress respectively. The result for supervisor-subordinate relationship shown negative standard coefficient beta (B= -0.213), while t-value is 1.276 at p>0.05, whereas for role ambiguity, standard coefficient beta (B= 0.225) and the t-value is 1.408 at p>0.05. Type A and type B personality have no significant moderating effect between work related factors and stress, but act as stressor in this study. The result supported the Person-Environment theory that officers experiencing job stress towards accommodating higher job demand in the organization. The outcome of this study expected to expand the knowledge on impact and influence of stress factors which utilized as reliable input to formulate approaches to reduce the impact of stress and improve efficiency in the organization.